Legal Aspects of e-commerce in the Law on Electronic Information and Transactions - Muhammad Arrullah Safriawan (Focus Journal : Law Review, 2024)
This study aims to discuss the Legal Aspects of e-commerce in Law Number 11 of 2008 concerning Electronic Information and Transactions. In today's modern times, there are many sophisticated technologies where many people today can make electronic transactions. The research method used in this study is a type of normative legal research based on books and applicable laws and regulations. The results of this study show the need for legal aspects related to e-commerce because basically there are still many shortcomings in carrying out a protection of people who make electronic transactions. Examples of cases related to problems in e-commerce practices are in the case of differences between goods sent and goods ordered, usually the way of settlement is through the return of goods sent. In this case, using inter-package services. However, there are usually obstacles in the return process. The obstacle that usually occurs is the late delivery of goods that should already be in the manufacturer. These obstacles are usually caused by several factors, one of which is the goods lost during delivery.